Psychological burnout among teachers of social sciences in schools (Journal of the College of Basic Education, 2023)
Increased interest in the phenomenon of psychological burnout in the service profession, especiallyeducation, and this phenomenon can be neutralized procedurally as negative changes in attitudes and behaviorrelated to the individual as a response to work pressure, and among its important manifestations, for exampleLoss of interest in working in a routine manner, lack of motivation, resistance to change, loss ofinventiveness. In order to confirm the existence of the phenomenon of burnout among teachers of social sciences.For the secondary stage, the researcher designed a questionnaire containing (28) items that dealt with the sources of pressure inThe teaching profession and these resources are:1- Students behavior 2- Teachers' relationship with each other 3-. Teachers' relationship with the administration.4- The teacher's relationship with the profession 5-. 6- Self conflicts. Psychological symptoms of stress.To answer the research questions, a comparison was made on the basis of gender and teaching experience.The study revealed that there are differences between male and female teachers in the combustion phenomenon.self.Because of the importance of this topic, it needs focus and shed light on it by researchers.in educational and psychological specializations.